2008
DOI: 10.1007/s10815-008-9283-5
|View full text |Cite
|
Sign up to set email alerts
|

The presence of bacteria species in semen and sperm quality

Abstract: Sperm bacterial contamination is quite frequent and could contribute to the deterioration of the sperm quality of infertile men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
182
3
16

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(226 citation statements)
references
References 27 publications
25
182
3
16
Order By: Relevance
“…Mehta et al (46) isolated some pathogenic bacteria from semen samples of male partners in infertile couples, including Enterococcus faecalis, micrococci, and alpha-haemolytic streptococci. Other studies mentioned that the contamination and colonization of some bacteria in the male urogenital tract, rather than infection, could also contribute to the decrease in sperm quality (47,48).…”
Section: Male Genital Tract Infection and Bacteriospermiamentioning
confidence: 99%
See 3 more Smart Citations
“…Mehta et al (46) isolated some pathogenic bacteria from semen samples of male partners in infertile couples, including Enterococcus faecalis, micrococci, and alpha-haemolytic streptococci. Other studies mentioned that the contamination and colonization of some bacteria in the male urogenital tract, rather than infection, could also contribute to the decrease in sperm quality (47,48).…”
Section: Male Genital Tract Infection and Bacteriospermiamentioning
confidence: 99%
“…It has also been demonstrated that E. coli can start the apoptotic process by activating several caspases, proteases responsible for mitochondrial changes, alterations in membrane symmetry, and DNA fragmentation (48).…”
Section: The Effects Of Bacterial Infection On Sperm Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Moretti et al [101] examined ejaculate samples from infertile patients and detected Enteroccocus faecalis and Escherichia coli most frequently and, at lower frequencies, Streptococcus agalactiae, Ureaplasma urealyticum, Staphylococcus epidermidis, Streptococcus anginosus, and Morganella morganii. With the exception of U. urealyticum, the microorganisms are classed with the nonspecific saprophytic microflora and are not addressed in a conventional testing of infertility patients.…”
Section: Bacterial Infection Of the Ejaculatementioning
confidence: 99%